CASE Tools as Organizational Change: Investigating Incremental and Radical Changes in Systems Development - Orlikowski, Wanda J. (MIS Quarterly, 1993)
This paper presents the findings of an empirical study into two organizations’ experiences with the adoption and use of CASE tools over time. Using a grounded theory research approach, the study characterizes the organizations’ experiences in terms of processes of incremental or radical organizational change. These findings are used to develop a theoretical framework for conceptualizing the organizational issues around the adoption and use of these tools—issues that have been largely missing from contemporary discussions of CASE tools. The paper thus has important implications for research and practice. Specifically, the framework and findings suggest that in order to account for the experiences and outcomes associated with CASE tools, researchers should consider the social context of systems development, the intentions and actions of key players, and the implementation process followed by the organization. Similarly, the paper suggests that practitioners will be better able to manage their organizations’ experiences with CASE tools if they understand that such implementations involve a process of organizational change over time and not merely the installation of a new technology.